The types of bilingualism that a bilingual represents have a significant impact on the volume and types of interference and resultant errors - Martyńska, Małgorzata (Scripta Neophilologica Posnaniensia, 2018)
The types of bilingualism that a bilingual represents have a significant impact on the volume and types of interference and resultant errors